ZnWO4 scintillators for cryogenic dark matter experiments - Kraus, H; Danevich, F; Henry, S; Kobychev, V; Mikhailik, V; Mokina, V; Nagorny, S; Polischuk, O; Tretyak, V (2009)
The scintillation properties of a zinc tungstate crystal, shaped as a hexagonal prism (height 40 mm, diagonal 40 mm) were determined. An energy resolution of 10.7% for the 662 keV γ-line of 137Cs was measured with the scintillator placed in a light collection setup similar to that used by the CRESST dark matter search. The light output and decay kinetics of ZnWO4 were examined over the temperature range 7-300 K and confirmed to be competitive with those of CaWO4. The radioactive contaminations of the ZnWO4 scintillator measured in the Solotvina Underground Laboratory do not exceed 0.1-10 mBq/kg (depending on radionuclide). Our study highlights the excellent feasibility of this ZnWO4 scintillator for a cryogenic dark matter experiment. © 2008 Elsevier B.V. All rights reserved.